Toxicological safety assessment of a water extract of Lithocarpus litseifolius by a 90-day repeated oral toxicity study in rats - Jinfeng Ma; Yujia Wei; Jingfeng Sun; Fang Tan; Penghe Liu; Guangqiu Qin (Frontiers Media S.A., 2024)
Lithocarpus litseifolius although known as "Sweet Tea" (ST), has been traditionally accepted as a daily beverage and used as a folk medicine in southern China with little understanding of its potential toxicity. This study evaluated the safety of a water extract of ST by a subchronic toxicity study in Sprague-Dawley rats. A total of 80 rats were randomized divided into 4 groups with 10 males and 10 females in each group, treated with 2000, 1,000, 500 and 0 mg/kg body weight of ST extract by gavage for 90 days, respectively. The results of the study showed that ST extract did not induce treatment-related changes in the body and organ weight, food intake, blood hematology and serum biochemistry, urine indices, and histopathology in rats. The NOAEL of ST extract was observed to be 2000 mg/kg/day for rats of both sexes. These results indicated that ST extract was of low toxicity in the experimental conditions of the current study and had the potential for application in food-related products.